Discrepancies between antemortem computed tomography scan and autopsy findings of traumatic intracranial haemorrrhage at Pietersburg Hospital forensic pathology Department - Hlahla, Mmachuene I (University of Limpopo, 2019)
Traumatic intracranial haemorrhages are common, carry a high mortality rate and are therefore commonly known in the practice of forensic pathology as unnatural deaths. Studies have demonstrated a significant decrease in mortality rate among patients who received surgical interventions compared to patients who were treated medically. Missed or mis-diagnoses, which may be apparent during an autopsy procedure, present possible missed treatment opportunities. Aim/objective and methods The study investigated the discrepancy rate and discrepancy pattern of diagnosis between antemortem brain computed tomography (CT) scan findings and autopsy findings in deceased patients with traumatic intracranial haemorrhage (TIH). A quantitative retrospective descriptive study was conducted based on bodies presented with TIH at Pietersburg Hospital Forensic Pathology Department. A total of consecutive 85 cases with antemortem CT (ACT) scan findings were compared to autopsy findings using percentage agreement and Cohen’s kappa statistics. Results and conclusion There was a fair overall agreement (k=0.38) with overall discrepancy rate of 24.74%, ranging from 9.41% to 34.12% for individual TIH between ACT scan and autopsy findings. Subarachnoid haemorrhage had the lowest agreement between the ACT scan and autopsy findings for TIH. Patient and doctor factors associated with the discrepancies were assessed. Those associated factors, if addressed, may have a positive impact on patient outcome. As far as the debate on non-invasive autopsy procedure is concerned, as a result of existing discrepancy rate, we conclude that ACT should not be used alone in the determination of cause of death but may be used in conjunction with autopsy findings.
Thesis (MMED. (Forensic Medicine)) --University of Limpopo, 2019
Keywords: Discrepancy rate; Autopsy; Antemortem computed tomography; Traumatic intracranial haemorrhage; Hemorrhage; Head --Wounds and injuries.; Forensic medicine